O curso de Administração de Empresas frente aos novos paradigmas educacionais - Silva, Ana Mônica Beltrão da (2005)
The objective of the dissertation is to place the Course of Administration of Companies inside of the reality of the neoliberal capitalism, the international agents' of financing demands, FMI and World Bank, that place the education as an educational market, to show the importance of the Course of Administration of Companies in the job market and at the same time, to place him/it front to the new educational paradigms. And to clear that the old paradigms, autocracy and distrust, conformism and individualism used in the managerial administration, no longer they are framed more in current reality, to look for new alternatives and to apply them to the administration of new businesses in a world more and more complex, globalization and under influences of radical changes promoted by the Third Industrial Revolution, the economy of the information. And that, with the implantation of the flexibility of tasks and functions in the work doesn't pronounce with an organization whose structure was conceived as a net of positions, where each position was already per-defined in terms of attributions and hierarchical relationships. And with the coming of the economy globalization and to strong influence of the progresses of the communication means and of the allied computer science resources to changes of paradigm of the science they don't hold a teaching in the universities that you is characterized by a practice pedagogic conservative, repetitive and critical and, for that it is that you intends a change in the Courses of Administration by a Pedagogic Project in consonance with the demands of the contemporary society, observing the guidelines of the Law 9394/98 in what refers to the higher education and the orientations of the National Council of Administration, the Course of Administration of FACH, has as commitment the human being integral formation, that constitutes instrument of construction of the citizenship - the human competence of doing subjects , professionals with social and ethical responsibility professional.